Pengaruh Literasi Keuangan, Persepsi Kegunaan, dan Kemudahan Penggunaan pada Minat Penggunaan Quick Response Code Indonesian Standard (QRIS) Dalam Transaksi Keuangan (Studi Kasus Pada Mahasiswa FEB Unisma Tahun 2019) - Lailla Anggriani; Nur Diana; Dewi Diah Fakhriyyah (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This research aims to analyze the influence of financial literacy, perceived usefulness, and ease of use on the intention to use Quick Response Code Indonesian Standard (QRIS) in financial transactions. A quantitative correlational method was employed for this study. The research sample consisted of 90 active students from the Faculty of Economics and Business at the Islamic University of Malang in 2019. Data were collected using a questionnaire distributed through Google Form. Multiple linear regression analysis was utilized as the data analysis method. The research results revealed a significant influence of financial literacy, perceived usefulness, and ease of use on the intention to use QRIS in financial transactions. The implications of this study provide theoretical and practical contributions to the understanding of QRIS usage based on the Technology Acceptance Model (TAM) theory for students, academics, Bank Indonesia, and for QRIS user services.Keywords: Financial literacy, perceived usefulness, ease of use, intention to use, Quick Response Code Indonesian Standard (QRIS), financial transactions.